Improving Mineral Mining License System in North Sumatera Indonesia - Ginting, Erika Sari; Pramono, Retno Widodo Dwi (CAKRAWALA, 2020)
The establishment of One-stop Service in Indonesia is expected to improve the quality of licensing process. In the mining license system, the investors still find some obstacles. Meanwhile the resources of mining area in Indonesia still attractive to the investors. Therefore, it is obvious that there is room for improvements in the mining license system. This research uses the Soft System Methodology. The primary data are obtained by interviewing the stakeholders and the secondary data are gathered through document review. The result shows that there are several problems in mining license system in North Sumatera. The problems occur because of the absence of local regulation in the mining license system, lack of coordination and unfit regulation. To improve the service in mining license system, the government need to issue a new regulation on mining license system, arrange a coordination system and issue new regulation on rock mining license.